T-shaped macular buckling combined with 25G pars plana vitrectomy for macular hole, macular schisis, and macular detachment in highly myopic eyes. Issue 3 (27th May 2016) - Mura, Marco; Iannetta, Danilo; Buschini, Elisa; de Smet, Marc D
Abstract : Objective: To report our experience using the T-shaped macular buckle (MB) with or without pars plana vitrectomy (PPV) as primary surgery or with a previous failed surgical approach in patients affected by high myopia and macular hole (MH) with or without macular detachment and with or without macular schisis. The primary goal was to evaluate complete closure of the MH and reattachment of the retina. Design: Retrospective case series of 21 consecutive patients who underwent T-shaped MB implant alone or combined with PPV at the Academic Medical Center in Amsterdam, The Netherlands, between January 2013 and November 2014. The mean axial length was 31.22 mm. The mean follow-up period was 7 months. Results: Retinal reattachment was achieved in 100% of cases while MH closure was achieved in 90.5%. No major perioperative complications were observed. Best corrected visual acuity improved in 71.4% of patients. Conclusions: MB combined with PPV should be considered as the preferred surgical approach both in primary and recurrent retinal detachment secondary to MH in high myopic eyes.